Case fatality rate among elderly covid-19 patients in Kelantan, Malaysia in 2020 – 2022 and its associated factors - Abdullah, Muhammad Saufi (2023)
Background: The COVID-19 pandemic has significantly impacted global mortality rates, with the elderly population experiencing disproportionate effects. Compared to younger individuals, elderly individuals face a higher susceptibility to severe symptoms, hospitalization, and higher case fatality rates. Objectives: The aim of this study is to determine the case fatality rate and identify factors contributing to death due to COVID-19 among the elderly population in Kelantan, Malaysia, from 2020 to 2022. Methodology: The study was conducted utilizing secondary data from the national COVID-19 database for the period of 1st April 2020 to 31st March 2022. This study involved cross-sectional and case-control study designs. Simple random sampling was employed to ensure a representative dataset. Data analysis was carried out using simple and multiple logistic regression methods. Results: The study included 28,295 elderly patients (≥60 years old). These patients were divided into case and control groups, with 780 patients randomly selected from the case group and 3,120 patients from the control group. The case fatality rate for the elderly population with COVID-19 in Kelantan during this period was 3.6%. Out of 28,295 elderly patients, 27,204 survived the infection, 1,024 died due to COVID-19, and 67 died with COVID-19. Multiple logistic regression analysis revealed significant factors associated with death due to COVID-19, including age at diagnosis (adjusted OR 1.09; 95% CI: 1.07, 1.10; p = <0.001), one dose of the COVID-19 vaccine (adjusted OR 0.70; 95% CI: 0.51, 0.97; p = 0.034), two doses of the COVID-19 vaccine (adjusted OR 0.13; 95% CI: 0.11, 0.16; p = <0.001), and three doses of the COVID-19 vaccine (adjusted OR 0.004; 95% CI: 0.001, 0.030; p = <0.001). Conclusions: The case fatality rate for the elderly population with COVID-19 in Kelantan remains high. The findings in this study offer valuable insights into factors influencing COVID-19 mortality among this vulnerable group. By recognizing the importance of age at diagnosis and vaccination status in determining outcomes for elderly patients, healthcare professionals and policymakers can devise targeted interventions and public health strategies aimed at reducing mortality risk and improving the overall prognosis for this at-risk population.